Peningkatan Kinerja Keberlanjutan dengan Strategi Eco-efficiency: Studi Kasus di UKM Batik SS Jogja - Hartini, Sri; Yulianto, Prasetyo (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2020)
Batik is a World Cultural Heritage. However, the production process is suspected to have a negative impact on the environment. This study aims to analyze the Batik production process using an eco-efficiency approach. The identification stage is carried out by identifying the non-product output costs. The environmental impact analysis was carried out by means of a life cycle assessment (LCA) using the eco-cost and eco-mapping methods. The causal analysis stage was carried out with a fishbone diagram. The problem area occurs in the stamping, coloring and washing processes. LCA processing using simapro v7.1.8 software concluded that there was a negative impact on the global warming (CO2 eq) category of 14,804.2 kg and aquatic ecotoxic (TEG eq) of 10,241,717 kg or equivalent to an eco-cost of Rp 700,394,880 / year. Recommendations for improvement by making used candleÂ  container, adding assignments for one of the workers, and creating a simple waste treatment system with the principle of aerobic biological treatment. This research provides benefits economically, environmentally and socially. The recommendations given are estimated to reduce the non-product output ratio by 0.01224, with an economic profit of around Rp 25,571,892 / year.